2018
DOI: 10.1111/ap.12303
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Parental Intentions to Enrol Their Children in Swimming Lessons Using an Extended Theory of Planned Behaviour

Abstract: Objective: For children under 15 years, drowning accounts for higher worldwide mortality rates than any other injury source. Our aim was to determine the predictors of parents accessing learn-to-swim classes for their children and whether parents' overall motivation contributed to the explanation of behavioural intention. Using an extended version of the theory of planned behaviour (TPB), incorporating past behaviour and parents' health motivation, barriers and benefits associated with parents' intentions to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Data time periods ranged from 1987 to 30 June 2019, with one study comparing by remoteness in Western Australia (WA) from 1953‐1962 to 1983‐1992 37 . Studies varied in their use of classification systems for remoteness with 20 studies using standard classification systems, 3,12,18‐27,30,38‐43,46 four studies modifying existing standard classification systems 16,29,44,45 and eight studies using their own classification system (Table ) 28,31‐37 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data time periods ranged from 1987 to 30 June 2019, with one study comparing by remoteness in Western Australia (WA) from 1953‐1962 to 1983‐1992 37 . Studies varied in their use of classification systems for remoteness with 20 studies using standard classification systems, 3,12,18‐27,30,38‐43,46 four studies modifying existing standard classification systems 16,29,44,45 and eight studies using their own classification system (Table ) 28,31‐37 …”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies made 27 recommendations regarding prevention strategies for rural drowning. 12,22,23,[28][29][30][31][34][35][36]39,[43][44][45] Of these, only one detailed an evaluated strategy, 30 a water safety training program (including signage and water safety resources) delivered to 11 remote Australian communities. The study found flexible, community-led delivery was a (Table 5).…”
Section: Prevention Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Question content and design were also influenced by other studies that have tested aspects of the Theory of Planned Behaviour from various literatures (e.g. Irwin, O'callaghan, & Glendon, 2018;Menozzi, Sogari, Veneziani, Simoni, & Mora, 2017).…”
Section: Intention and Belief Questionnairesmentioning
confidence: 99%